Perhitungan Penilaian Tingkat Kepuasan Pelanggan Dengan Menerapkan Algoritma K-Means - Dini Puspita Dewi; Indyah Hartami Santi; Wahyu Dwi Puspitasari (LPPM STIKI MALANG, 2023)
All business actors compete to find as many customers as possible and of course provide the best service, one of which is by considering the level of customer satisfaction. The aim of this research is to understand the level of customer satisfaction more effectively and provide valuable information for Jaya Fotocopy in making decisions to improve service quality in more detail. By grouping customer satisfaction into appropriate categories, customer management based on purchasing patterns, time of visit, and service received can identify areas that require improvement to ensure better customer satisfaction using the K-means algorithm. The results of this research classify customer satisfaction with dimensions of responsiveness of 76.32%, reliability of 91.10%, empathy of 90.11%, guarantee of 92.09%, and real evidence of 93.08%. Meanwhile, the specificity test of the K- Means algorithm method can classify customer dissatisfaction with the dimensions of responsiveness 27.17%, reliability 19.11%, empathy 19.00%, guarantee 19.50%, and real evidence 20.29%. From the results of the data obtained, Jaya Fotocopy must increase the dimension of responsiveness to only reach 27.17%. Jaya Photocopy needs to ensure that customer service is more responsive to customer needs and requests. This could include improvements in response times to customer questions or complaints and improving the ability to resolve customer issues quickly. Apart from that, Jaya Photocopy must also carry out further analysis to understand the causes of customer dissatisfaction in the dimensions of responsiveness, reliability, empathy, guarantees and concrete evidence. With a deeper understanding of the problem, more specific remedial steps can be taken. Jaya Photocopy can also improve communication with customers to hear their input and feedback regularly to find out what customers expect.